1998
DOI: 10.1111/j.1945-5100.1998.tb01720.x
|View full text |Cite
|
Sign up to set email alerts
|

Nebular or parent body alteration of chondritic material: Neither or both?

Abstract: Abstract-Discussions of meteorite properties often concern whether they are the result of 'hebular'' or "parent body" processes, but several decades of research have not resolved the issue. Part of the problem is that any gas-phase reaction involving meteoritic materials thought to have occurred is automatically assumed to be nebular, even though the most primitive solar system objects are water-and volatile-rich and could easily generate vapors. Reactions important in meteorite genesis are those involving (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…(2000), silicate liquids calculated to form at 1000x dust enrichments and 10-3 bar only contained~10 ppm H20 at 1460 K. Water does not become an important alteration reactant in the solar nebula or on parent bodies unless the temperature is below 500 K (e.g., references cited in Bischoff, 1998;Sears and Akridge, 1998). This suggests that zoning of H and, by extension elements that strongly correlate with H, occurred at low temperatures, probably in the parent asteroid where aqueous processes are known to have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…(2000), silicate liquids calculated to form at 1000x dust enrichments and 10-3 bar only contained~10 ppm H20 at 1460 K. Water does not become an important alteration reactant in the solar nebula or on parent bodies unless the temperature is below 500 K (e.g., references cited in Bischoff, 1998;Sears and Akridge, 1998). This suggests that zoning of H and, by extension elements that strongly correlate with H, occurred at low temperatures, probably in the parent asteroid where aqueous processes are known to have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…(Pisani 1864;Brearley 2006;Bland et al 2009). The magnetites were earlier thought to have condensed from the cooling solar nebula (Larimer and Anders 1967;Sears and Akridge 1998). It was also suggested that these water-bearing minerals are the byproducts of the aqueous alteration between water and anhydrous minerals in the cooling solar nebula (Grossman and Larimer 1974;Weisberg et al 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the various components within the meteorites have been subject to one or more episodes of alteration either in the solar nebula or later within a parent body, or perhaps in both environments (Krot et al 1995;Bischoff 1998;Sears and Akridge 1998;Zolensky et al 1997). Radiometric dating of the alteration events may allow greater insight into the nature of the environment in which alteration occurred (e.g., very late ages would imply a parent body location rather than nebular).…”
Section: Introductionmentioning
confidence: 99%